2015: The beginning of the end of the war against malaria - Richard Tjan (Faculty of Medicine, Universitas Trisakti, 2015)
In May 2015 the 62th World Health Assembly formulated a global malaria strategy for 2016-2030 aiming to “reduce the global disease burden by 40% by 2020, and by at least 90% by 2030. It also aims to eliminate malaria in at least 35 new countries by 2030”.(1) As a reminder, it was 60 years ago that the Eighth World Health Assembly decided in 1955 to shift from malaria control to malaria eradication, with the aim to make many areas of free of malaria “within 10 to 15 years”.(2) This has yet to be accomplished in many malaria endemic countries such as Indonesia, where the earliest program was the malaria eradication program of 1959, evolving into the malaria control program, the roll-back malaria program, and finally in 2012 into the malaria elimination program.(3) In view of the ever-present insecticideresistance